Down-regulated Genes in Mouse Dental Papillae and Pulp - Sasaki, H.; Muramatsu, T.; Kwon, H.-J.; Yamamoto, H.; Hashimoto, S.; Jung, H.-S.; Shimono, M. (Journal of dental research, 2010)
Important factors involved in odontogenesis in mouse dental papillae disappear between the pre- and post-natal stages of development. Therefore, we hypothesized that certain genes involved in odontogenesis in dental papillae were subject to pre-/post-natal down-regulation. Our goal was to identify, by microarray analysis, which genes were down-regulated. Dental papillae were isolated from embryonic 16-day-, 18-day- (E16, E18), and post-natal 3-day-old (P3) murine first mandibular molar germs and analyzed by microarray. The number of down-regulated genes was 2269 between E16 and E18, and 3130 between E18 and P3. Drastic down-regulation (fold change > 10.0) of Adamts4, Aldha1a2, and Lef1 was observed at both E16 and E18, and quantitative RT-PCR revealed a post-natal reduction in their expression (Adamts4, 1/3; Aldh1a2, 1/13; and Lef1, 1/37). These results suggest that down-regulation of these three genes is an important factor in normal odontogenesis in dental papillae.